Peningkatan Keterampilan Berpidato Persuasif Siswa Kelas IX SMP 1 Kota Bengkulu Melalui Model Pembelajaran Berbasis Masalah (Problem-Based Learning) Berbantuan Media Podcast Video - Topia, Anisa; Andra, Vebbi; Friantary, Heny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of persuasive speaking skills among ninth-grade students at SMP 1 Bengkulu City, which was attributed to factors such as stage fright, limited ability to construct logical arguments, and a lack of interactive media in classroom instruction. This study aims to improve students’ persuasive speaking skills through the application of the Problem-Based Learning (PBL) model integrated with the use of video podcast media. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, covering the stages of planning, implementation, observation, and reflection. The research subjects consisted of 32 ninth-grade students. Data were collected through public speaking performance tests, activity observation sheets, and student response questionnaires, then analyzed using descriptive qualitative and quantitative methods. The results showed a significant, gradual improvement in persuasive public speaking skills. In the pre-cycle baseline condition, the class average score was only 64.2, with a classical mastery rate of 34.4% (11 students met the criteria). After implementing the intervention in Cycle I, the average score increased to 72.8 with a classical mastery rate of 62.5% (20 students met the criteria). Weaknesses identified in Cycle I were addressed in Cycle II, resulting in a significant jump in the class average to 81.4 with a classical mastery rate of 87.5%. Based on these findings, it can be concluded that the synergy between the Problem-Based Learning model and video podcasts is effective in improving persuasive speaking skills, fostering critical thinking regarding factual issues, boosting self-confidence, and creating a collaborative learning environment.